􏰊􏰋􏰌􏰍􏰎 􏰏􏰐􏰑􏰒􏰓􏰔􏰊􏰕􏰖􏰊􏰋􏰌􏰍􏰎 􏰏􏰐􏰑The works of Mykola Lysenko in Galina Lewicka’s performing and journalistic activity - 􏰊􏰋􏰌􏰍􏰎 􏰏􏰐􏰑􏰒􏰓􏰔􏰊􏰕􏰖􏰊􏰋􏰌􏰏􏰐􏰑􏰒􏰓􏰔􏰊􏰕􏰖Olha Kuzentsova (Edukacja Muzyczna, 2019)
The article analyses the achievements of Galina Lewicka (1901–1949) in the fields of piano performance and journalism. She promoted the artistic output of Mykola Lysenko (1842–1912) – a Ukrainian composer, teacher, pianist, conductor and folklorist. As one of the greatest Galician pianists, Lewicka took part in a series of concerts held in the years 1930–1940 to honour Lysenko, during which she performed his First rhapsody – a remarkably difficult piece created on the basis of folk dumas. In 1937, her interpretation of this work performed in Lviv was enthusiastically received by several critics. She wrote about the experience of performing the piece in the article Lysenko’s “First rhapsody.” Lewicka also performed other works written by the composer, including vocal-instrumental pieces played with the famous singer Michaił Gołyński. The pianist is also https://orcid.org/0000-0003-2494-2767 Olha KUZNETSOVA] the author of a book for young people entitled Mykola Lysenko, which she published under the pseudonym of Oksana Piatygorskaya . Furthermore, she wrote an article about a jubilee exhibition for the 100th anniversary of Lysenko’s birth, which was held in Lviv in 1942, and a review of a concert that took place in an opera theatre as part of the event. Lewicka’s promoting activity is an expression of her sincere respect for Mykola Lysenko – the founder of the Ukrainian school of composition, an activist and a patriot. The pianist’s achievements in performing drew the attention of numerous authors: Oleg Krysztalski, Tetiana Worobkewycz, Natalia Kaszkadamowa, Oksana Ditczuk and others. None of them, however, paid attention to her accomplishments in the field of promoting Lysenko’s activity and works . Hence the need for a comprehensive study of this subject. The aim of this article is, therefore, to present Lewicka’s achievements in the field of performing Lysenko’s pieces and to determine the degree to which she contributed to popularizing the knowledge of the composer in Galicia.